2018
DOI: 10.7567/jjap.57.11uf15
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial ferroelectric Y-doped HfO2 film grown by the RF magnetron sputtering

Abstract: YO1.5-doped HfO2 films were deposited on yttria-stabilized zirconia substrates by RF magnetron sputtering at room temperature and under various atmosphere conditions. The deposited films were treated by rapid thermal annealing under both O2 and N2 flows. Epitaxial films with the orthorhombic phase, which is expected to exhibit ferroelectricity, are obtained under all conditions. The deposition in Ar atmosphere provided good ferroelectricity, while the deposition with O2 resulted in a low breakdown voltage inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
2
15
0
Order By: Relevance
“…This result, which suggests that oxygen vacancies are convenient to stabilize the metastable orthorhombic phase, are in agreement with observations done with polycrystalline films [46][47] and epitaxial films obtained by RTA of amorphous films. 45 Mimura et al 48 confirmed ferroelectricity by polarization loops, with high Pr of 14.5 µC/cm 2 in films on ITO/YSZ (111), and much lower polarization in films on ITO/YSZ(001). Although it is known that some fluorite oxides as CeO2 can grow epitaxially at room temperature, 49 the result reported by Mimura et al 48 was surprising and further studies are required to understand the mechanism that allow epitaxial growth of the metastable phase at room temperature.…”
Section: Solid Phase Epitaxymentioning
confidence: 95%
See 1 more Smart Citation
“…This result, which suggests that oxygen vacancies are convenient to stabilize the metastable orthorhombic phase, are in agreement with observations done with polycrystalline films [46][47] and epitaxial films obtained by RTA of amorphous films. 45 Mimura et al 48 confirmed ferroelectricity by polarization loops, with high Pr of 14.5 µC/cm 2 in films on ITO/YSZ (111), and much lower polarization in films on ITO/YSZ(001). Although it is known that some fluorite oxides as CeO2 can grow epitaxially at room temperature, 49 the result reported by Mimura et al 48 was surprising and further studies are required to understand the mechanism that allow epitaxial growth of the metastable phase at room temperature.…”
Section: Solid Phase Epitaxymentioning
confidence: 95%
“…Suzuki et al investigated the influence of the atmosphere in sputtering at room temperature and rapid thermal annealing for crystallization. They deposited Hf 0.93 Y 0.07 O 2 films, around 24 nm thick, by RF magnetron sputtering under 200 mTorr of pure Ar or Ar/O 2 = 100.…”
Section: Solid Phase Epitaxymentioning
confidence: 99%
“…Apart from PLD, radio frequency sputtering has also been successful in fabricating epitaxial hafnia thin films on 10 wt% Sn-doped In 2 O 3 (ITO)/YSZ, usually grown at room temperature followed by rapid thermal annealing. [33,40,78] Given most of the results were obtained via PLD, mainly epitaxial hafnia thin films grown by PLD were discussed in the following.…”
Section: Epitaxial Hafnia Thin Filmmentioning
confidence: 99%
“…In order to solve these problems, other deposition methods, including physical vapor deposition (PVD), chemical solution deposition (CSD) and PLD have been explored [21,43] . A comparison of these methods is shown in Table 2 [63,[103][104][105][106] .…”
Section: Film Deposition Methodsmentioning
confidence: 99%